The Role of Marketing Automation Platforms and AI Chatbots in Enhancing the Effectiveness of Digital Marketing Strategies in E-commerce: A Socio-Technical Perspective - Feronika Arfianingrum; Yeni Kartika Dewi Nurjana; Siti Mujanah; I Made Suparta (PT Inovasi Pratama Internasional, 2026)
Rapid advances in technology, particularly Artificial Intelligence (AI), have catalyzed a revolution in digital marketing operations within the e-commerce sector. Modern consumer engagement now relies heavily on digital infrastructures that offer personalized experiences and accelerated response times. Consequently, this research investigates the strategic role of marketing automation systems and AI-driven chatbots as socio-technical drivers to enhance the efficacy of digital marketing initiatives. Adopting an interpretive qualitative literature review methodology, this study regularly evaluates academic works published between 2021 and 2026. The analysis identifies four critical dimensions of digital marketing: automation as a meaning-making framework, chatbots as relational touchpoints, the necessity of human-AI integration, and ethical oversight as a prerequisite for sustainability. This study offers a conceptual contribution by positioning AI not merely as a tool for operational speed, but as a transformative socio-technical instrument that fosters a more value-oriented and accountable e-commerce environment. The findings demonstrate that marketing success is contingent upon more than just technical processes; it requires a balanced optimization of algorithmic functions and human managerial reflexivity